2006
DOI: 10.1111/j.1551-2916.2006.01111.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of a Nanoparticle Suspension for Freeze Casting

Abstract: Poly(acrylic acid) (PAA) dispersant concentration, suspension pH, and Al2O3 solids loading effects on PAA adsorption onto Al2O3 nanoparticles were studied; the stability and rheology of the Al2O3 nanoparticle suspensions were examined. The most desirable suspension conditions were 7.5–9.5 for pH and 2.00–2.25 wt% of Al2O3 for the PAA concentration. Electrical double‐layer thickness and PAA adsorption layer thickness comparison showed that electrosteric stabilization was dominant. 45.0 vol% Al2O3 solids loading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 23 publications
1
57
0
Order By: Relevance
“…This suggests that the electrostatic interaction between particles is not the main reason leading to the enhancement of viscosity. Lu et al [22,23] supposed that the carboxyl groups can interact with the hydroxyl groups to form link structure by hydrogen bonding. Therefore, the differences of viscosity between slurries with and without glycerol perhaps come from the effect of the links.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that the electrostatic interaction between particles is not the main reason leading to the enhancement of viscosity. Lu et al [22,23] supposed that the carboxyl groups can interact with the hydroxyl groups to form link structure by hydrogen bonding. Therefore, the differences of viscosity between slurries with and without glycerol perhaps come from the effect of the links.…”
Section: Resultsmentioning
confidence: 99%
“…The pore structure is mainly controlled by the ice nucleation, which is influenced by various parameters such as solution viscosity, concentration of the solute, growth velocity of ice crystals and pH. (Lu, Kessler, & Davis, 2006). Deville et al carried out detailed analysis of influence of func-tional groups on ice crystallization and found that the formation of various structures depends on functional groups (carboxylates, acetates and surfactants) (Deville, Viazzi, & Guizard, 2012).…”
Section: Results and Discussion 31 Scanning Electron Microscopymentioning
confidence: 99%
“…7 for the stabilized dispersions, but now in a form of a reduced (relative) viscosity. The reduced viscosity is the ratio of Al 2 O 3 (TM) dispersion viscosity to monomer viscosity as presented for example in references [24,29,30]. This representation enables the comparison between dispersions which are based on different solvent systems.…”
Section: Production Of Particles With Adsorbed Surfactants and Redispmentioning
confidence: 99%